A study of the possible distinction between "controlling eye" and "dominant eye" and the relation of both, with hand dominance, to reading achievement - Boos, Robert W (University of Ottawa (Canada), 1968)
Abstract not available.
Keywords: Education, Educational Psychology.; Education, Reading.